ON THE THREONIN IN THE MAIZE - GIRAL, JOSE; CRAVIOTO, RENE O (Universidad Nuevo Leon, NUEVO LEON, MONTERREY, MEX, 1941)
The estimation of threonin in the Mexican maize "Pepitilla," by Block's method, shows 522% of zein in whole flour extracted with alcohol The value for pure Pfanstiehl zein is of 563% Maize contains 5% of zein, or 0275% of threonin Care must be taken
CIENC MEX
Keywords: THREONIN, MAIZE; MULTIDISCIPLINARIA; AGRONOMIA; PRODUCCION DE CULTIVOS